A Multinational, Multicenter Study Mapping Models of Kidney Supportive Care Practice - Seren Marsh; Amanda Varghese; Charlotte M. Snead; Barnaby D. Hole; Daniel V. O’Hara; Neeru Agarwal; Elizabeth Stallworthy; Fergus J. Caskey; Brendan J. Smyth; Kathryn Ducharlet (Kidney International Reports)
Introduction: Kidney supportive care (KSC) integrates kidney and palliative care to improve quality of life for people with chronic kidney disease (CKD). Despite increasing interest and global advocacy to integrate KSC into kidney care, evidence to guide optimal care delivery is limited. Methods: This observational cross-sectional study used an online survey to describe current KSC models in Australia, Aotearoa-New Zealand, and the UK. Results: Between April and December 2022, 114 nephrology units responded (response rate 67%), with 66% having a dedicated KSC service (UK, 74%; Australia, 58%; and New Zealand, 67%). Many different health care professionals worked in KSC services with diversity in clinical resources and activities between units and across countries. Overall, funding for KSC services was low, with a median full time equivalent (FTE) per unit (standardized per 100 people receiving hemodialysis [HD]) of 0.51 (interquartile range [IQR], 0.17–1.05) and 4 units provided a service without allocated funding. The scope of KSC service was wide-ranging and prioritized activities included symptom management, psychological support, complex future treatment planning and discussion, and care coordination. There were no significant differences between countries in terms of location of care provision, frequency of review, referral patterns or discharge rates; however, there was variation described within countries. Conclusion: Models of KSC vary markedly across kidney units and between countries. Despite this variation, there was consistency in terms of clinical priorities which were person-centered and focused on physical and psychosocial well-being. Further research is required to evaluate the effectiveness of KSC provision, alongside improved funding methods to ensure sustainable and equitable KSC delivery.